1999
DOI: 10.1002/clc.4960221503
|View full text |Cite
|
Sign up to set email alerts
|

A dietary approach to prevent hypertension: A review of the dietary approaches to stop hypertension (DASH) study

Abstract: SummaryBackground: Populations eating mainly vegetarian diets have lower blood pressure levels than those eating omnivorous diets. Epidemiologic findings suggest that eating fruits and vegetables lowers blood pressure.Hypothesis: Two hypotheses were tested: (1) that high intake of h i t s and vegetables lowers blood pressure, and (2) that an overall dietary pattern (known as the DASH diet, or DASH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(140 citation statements)
references
References 10 publications
7
128
1
4
Order By: Relevance
“…The relation with weight loss was less strong owing to the small weight loss seen over 1 year (0.64 kg). For subjects with blood pressures greater than 130/85, the systolic blood pressure reduction of 13 mm Hg was similar to that reported for the DASH and PREMIER diets (Appel et al, 1997;Sacks et al, 1999;Chobanian et al, 2003), whereas those already with target blood pressures showed little effect. The blood pressure reductions were not altered when the seven completers on stable doses of blood pressure medication were removed.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The relation with weight loss was less strong owing to the small weight loss seen over 1 year (0.64 kg). For subjects with blood pressures greater than 130/85, the systolic blood pressure reduction of 13 mm Hg was similar to that reported for the DASH and PREMIER diets (Appel et al, 1997;Sacks et al, 1999;Chobanian et al, 2003), whereas those already with target blood pressures showed little effect. The blood pressure reductions were not altered when the seven completers on stable doses of blood pressure medication were removed.…”
Section: Discussionsupporting
confidence: 83%
“…As with the major diet and lifestyle blood pressure studies, the main effect was seen in those with the higher blood pressure (Appel et al, 1997(Appel et al, , 2003Sacks et al, 1999;Chobanian et al, 2003;Svetkey et al, 2005). Dividing the group into those with blood pressures above or below 130/ 85 mm Hg gave systolic blood pressure reductions of 13.271.7 versus 1.871.4 mm Hg, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Salt reduction may be difficult in populations using it for food conservation. The implementation of controlled diets like promoted in Dietary Approaches to Stop Hypertension (DASH) (46,47), may be difficult in SSA settings because those measures require change in preparation, conservation and other infrastructures and resources not available in SSA. Since the conservation of food in SSA can be difficult, fresh food should be promoted.…”
Section: Different Focus In Preventive Strategiesmentioning
confidence: 99%